Calcification markers and long-term outcomes of coronary artery bypass grafting - E. M. Stakhneva; E. V. Kashtanova; A. V. Kurguzov; N. A. Maslatsov; Ya. V. Polonskaya; I. S. Murashov; A. M. Chernyavsky; Yu. I. Ragino (Российский кардиологический журнал, 2021)
Aim. To assess the long-term outcomes of coronary artery bypass grafting (CABG) and their association with calcification biomarkers.Material and methods. The study included 129 men (mean age, 61,5±7,5 years) with coronary atherosclerosis who were admitted for CABG surgery. Patients were divided into 2 groups: with favorable and unfavorable (death, myocardial infarction, stroke, surgery) 5-year prognosis after surgery. Before the surgery, the blood concentrations of calcification biomarkers (osteoprotegerin, osteopontin, osteonectin and osteocalcin) were determined in all patients.Results. Long-term outcomes of myocardial revascularization were studied in 92 patients (71%). An unfavorable long-term 5-year period was identified in 28 men (30,4%). In men with an unfavorable 5-year prognosis, the blood osteocalcin level before CABG was 1,2 times higher than in men with a favorable one. Multivariate linear regression showed that the risk of a 5-year unfavorable prognosis for coronary atherosclerosis after myocardial revascularization was associated with the blood osteocalcin concentration, determined before CABG (B=0,018, R2=0,285, p=0,008).Conclusion. The data obtained indicate the relevance of continuing studies on osteocalcin, including with respect to its contribution to coronary atherosclerosis and calcification.